Infidelity Through Social Media as A Reason for Divorce - Moh Arhis Said S. Bulagi; Nurhadi; Usman Alfarisi; Fatma Nurmulia; Moh Khoirul Anam (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
In principle, everyone wants a normal and acceptable life in social life. Human beings naturally follow the rules of people's lives, including the rules in family life, but the social environment, position, social status, and experience can change a person. Similarly, in married life, the original situation can be so harmonious that it can turn into conflicts and quarrels when the husband commits an act of infidelity and the wife does the opposite. This reality is sometimes difficult to overcome, in fact, not a few households end up divorced. The author feels the need to raise the issue of infidelity as the reason for divorce in the South Jakarta religious court where there are still many lawsuits filed by both wives and husbands. This type of research is qualitative research or field research with a juridical and non-juridical approach, namely by conducting a search for the study of Law No. 1 of 1974 concerning marriage and also looking at the mutual benefits of the decision of the Panel of Judges. The results of the study show that: First, the ban on divorce in the South Jakarta Religious Court has several factors, including economic factors, moral crisis, and also infidelity factors. Second, the consideration of the Panel of Judges in deciding case No.503/Pdt.G/2019/PA.JS is to look at the facts at the trial, if the plaintiff's lawsuit can be proven correctly, it becomes the consideration of the Panel of Judges in deciding the case.